2020
DOI: 10.1186/s40463-020-00467-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of brachytherapy for margin control in oral tongue squamous cell carcinoma

Abstract: Background The aim of this study is to assess the feasibility and effectiveness of using peri-operative brachytherapy (BRTx) for positive/narrow margins present post primary surgical resection of oral tongue squamous cell carcinoma (OTSCC). Methods Prospective single-centre study of patients with OTSCC (T1–3, N0–3, M0) treated with resection of primary tumour ± regional nodal resection and intra-operative insertion of BRTx catheters. BRTx was administered twice daily at 40.8Gy/12Fr for ‘Positive’ (≤2 mm) mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Cox regression analysis indicated that recurrence and survival outcomes were not associated with margin status or the use of a specific dose of HDR-ISBT. Acute and late toxicity, secondary to HDR-ISBT, was minimal [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cox regression analysis indicated that recurrence and survival outcomes were not associated with margin status or the use of a specific dose of HDR-ISBT. Acute and late toxicity, secondary to HDR-ISBT, was minimal [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, revision surgery for positive or close margins is often challenging due to reconstruction of the primary tongue defect; in these cases, adjuvant RT is an option. Postoperative radiotherapy should be considered also in cases with lymphovascular and/or perineural invasion [ 30 ]. EBRT is associated with numerous acute and late side effects, including mucositis, dysphagia, xerostomia, and neck and mandibular necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Ianovski et al [ 30 ] evaluated postoperative HDR BT in patients with stage T1-3N0-3M0 disease, reporting 3- and 5-year OS rates of 75.6% and 59.1%; the DSS rates were 82.3% and 68.6%, respectively. In a preliminary study carried out by our group, postoperative HDR BT was indicated in the following cases: close or positive margins, presence of lymphovascular space or perineural invasion, poor differentiation, or tumour thickness > 5 mm [ 33 ].…”
Section: Introductionmentioning
confidence: 99%